2012
DOI: 10.1177/0022034512466262
|View full text |Cite
|
Sign up to set email alerts
|

Influence of S. mutans on Base-metal Dental Casting Alloy Toxicity

Abstract: We have highlighted that exposure of base-metal dental casting alloys to the acidogenic bacterium Streptococcus mutans significantly increases cellular toxicity following exposure to immortalized human TR146 oral keratinocytes. With Inductively Coupled Plasma-Mass Spectrometry (ICP-MS), S. mutans-treated nickel-based (Ni-based) and cobalt-chromium-based (Co-Cr-based) dental casting alloys were shown to leach elevated levels of metal ions compared with untreated dental casting alloys. We targeted several biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The atomic absorption spectrophotometer indicated that the values of ions release for Cu/Al alloy were significantly affected by exposure to S. mutans. This was also observed by the study of McGinley et al 14 who assessed the influence of S. mutans on dental alloys' toxicity and observed that ions release significantly increased in the presence of these bacteria, as it leads to pH reduction. On the other hand, MutluSagesen et al 22 stated that pH reduction is directly related to the great ions release by dental alloys.…”
Section: Mcginley Et Alsupporting
confidence: 71%
“…The atomic absorption spectrophotometer indicated that the values of ions release for Cu/Al alloy were significantly affected by exposure to S. mutans. This was also observed by the study of McGinley et al 14 who assessed the influence of S. mutans on dental alloys' toxicity and observed that ions release significantly increased in the presence of these bacteria, as it leads to pH reduction. On the other hand, MutluSagesen et al 22 stated that pH reduction is directly related to the great ions release by dental alloys.…”
Section: Mcginley Et Alsupporting
confidence: 71%
“…All specimens were polished with silicon carbide paper (400, 800, 1200 grit) with a grinder-polisher machine (M2V; Manfredi). The specimens were than cleaned in ethanol and deionized water in an ultrasonic cleaner for 5 minutes to remove contaminants and finally autoclave-sterilized as previously reported by Xin et al 42 and McGinley et al 17 Three solutions were prepared in order to evaluate chemical corrosion following the study by Mutlu-Sagesen et al 30 Three solutions were prepared to evaluate biocorrosion: a solution of 50% artificial saliva (pH 7.1), 45% tryptic soy broth (TSB; Oxoid) and 5% defibrinated horse blood (SS+B; Oxoid); a solution of 50% artificial saliva buffered with H3PO4 at pH 5.5, 45% TSB (SigmaAldrich) and 5% defibrinated horse blood (SS+AB; Oxoid); and a solution of 50% artificial saliva (pH 7.1), 45% TSB (Oxoid), and 5% defibrinated horse blood (Oxoid) added with 5 × 10 6 cells/mL E. corrodens (SS+BB). One sample of artificial saliva/TSB blood was adopted as blank reference.…”
Section: Methodsmentioning
confidence: 99%
“…9-12 The oral environment is an ideal place for corrosion because of the presence of saliva, acid bacterial plaque, changes in pH and temperature related to food or beverage intake, and the action of different medications. [13][14][15][16][17] The possibility of local alterations and the degree of severity at which they happen can be directly related to the alloy type and chemical state of the metal, the concentration, and the time of contact with mucosal tissues. 4,5 Base metal dental prostheses with monophasic alloys are less cytotoxic and inhibit human cell growth less than those with polyphasic alloys.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ACCEPTED MANUSCRIPT 11 and cause local symptoms, such as mucositis or even carcinogenicity and mutagenicity [40][41][42][43][44].…”
Section: Accepted Manuscriptmentioning
confidence: 99%